Penerbitan Sertipikat Hak Milik Oleh Kantor Pertanahan yang Berdasarkan Letter C (Studi Kasus pada Sertipikat Hak Milik Nomor 2092/Margosari di Kantor Pertanahan Kabupaten Kulonprogo) - Khanifan Khanifan (Lex Renaissance, 2020)
The research aims to determine the mechanism of issuance and legal certainty of Freehold Certificate No. 2092/Margosari on behalf of Ranu Dikromo which occupies Persil 62a P Class III on behalf of Sonto Permono. This study uses an empirical juridical approach, namely by examining secondary data first then followed by conducting research on primary data in the field. The results of the study conclude, first, the issuance of a certificate of property rights by the Kulon Progo Regency Land Office through stages based on the prevailing laws and regulations in Indonesia, however, many of the legal requirements for registration applications are manipulated and there are indications of illegal acts. Second, legal certainty SHM No. 2092/Margosari can still be contested in terms of its legality. The heirs of Sonto Permono who object to the issuance of the certificate can file a lawsuit at the local court. The court will decide on the basis of evidence that convinces the judge whether there has been an illegal act of issuing the certificate or affirming the issuance of the certificate.